АНАЛІЗ НАПРЯМКІВ РОЗВИТКУ ОСВІТИ В УКРАЇНІ (Педагогіка вищої та середньої школи, 2008)
The paper provides the analysis of the main form of development in Ukrainian education during the last one hundred years. Special attention is given to the quantitative indices of educational establishments of different levels and to the dynamics of student’s population growth. It studies the schoolteachers and university teachers stuff composition as well as the problems of pupils and students composition.